(untitled) (Journal of Organizational Psychology, 2021)
This research examines shared identity in the context of online training. Specifically, we examine the impact of perceived shared identity on social distance, operationalized as one’s willingness to work with another person and their willingness to recommend that person for a job. We conduct two studies of simulated online training and find that increased shared identity plays an important role in the online training process and that perceptions of trustworthiness mediate the relationship between shared identity and social distance. This research explores the impact social exchange has in online training when specifically examining social exchange between the trainer and trainee.